2015
DOI: 10.4238/2015.december.7.16
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and evolutionary analysis of nucleotide-binding site-encoding resistance genes in Lotus japonicus (Fabaceae)

Abstract: ABSTRACT. Nucleotide-binding site (NBS) disease resistance genes play a crucial role in plant defense responses against pathogens and insect pests. Many NBS-encoding genes have been detected in Lotus japonicus, an important forage crop in many parts of the world. However, most NBS genes identified so far in L. japonicus were only partial sequences. We identified 45 full-length NBS-encoding genes in the L. japonicus genome, and analyzed gene duplications, motifs, and the molecular phylogeny to further understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…ipaënsis , respectively, were excluded in this study because these sequences contained partial NBS domains or partial sequences. Song et al [ 5 ] demonstrated that incomplete NBS–LRR sequences used in analyses can lead to incorrect results. Among the full-length sequences, two AdNBS and nine AiNBS sequences were considered potential pseudogenes because they contained either a premature stop codon or a frameshift mutation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ipaënsis , respectively, were excluded in this study because these sequences contained partial NBS domains or partial sequences. Song et al [ 5 ] demonstrated that incomplete NBS–LRR sequences used in analyses can lead to incorrect results. Among the full-length sequences, two AdNBS and nine AiNBS sequences were considered potential pseudogenes because they contained either a premature stop codon or a frameshift mutation.…”
Section: Resultsmentioning
confidence: 99%
“…truncatula [ 6 ] and 71.77% NBS–LRR sequences in L . japonicas [ 5 ] had LRR domains. We found that AdNBS and AiNBS contained more LRR8 than LRR4, LRR3, LRR5, and LRR1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a stringent search against the NCBI conserved domain database CDD (MarchlerBauer et al, 2011) for identification of canonical CC and TIR domains. We did not classify as many NLRs into TNL, and especially CNL groups, as in previous studies (Supplemental Table S7; Monosi et al, 2004;Ameline-Torregrosa et al, 2008;Kim et al, 2012;Shao et al, 2014;Yu et al, 2014;Song et al, 2015;Sarris et al, 2016;Shao et al, 2016). We chose this conservative approach due to relatively poorly defined sequence composition and structure of especially the CC domains.…”
Section: The Brassicaceae Expression Shift Is Seen Across Multiple Nlmentioning
confidence: 99%
“…Encoding products of most disease resistance genes in plants are nucleotide-binding site leucine-rich repeat (NBS-LRR) proteins and diverse pathogens, including bacteria, viruses, fungi, nematodes, insects and oomycetes, are detected by NBS-LRR proteins. Researchers have studied this gene family in many plant genomes, including Arabidopsis thaliana [ 8 ], Glycine max [ 9 ], Lotus japonicas [ 10 ], Helianthus annuus [ 11 ], Oryza sativa [ 12 ] and Triticum aestivum [ 13 ]. Due to the difference of the N-terminal features, the NBS-LRR proteins can be divided into two subfamilies, TIR-NBS-LRR (TNL) and non-TNL-NBS-LRR (nTNL) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%